APLIKASI HIGH RESOLUTION MELTING ANALYSIS (HRMA) DALAM REAL-TIME PCR UNTUK DETEKSI CEMARAN DAGING TIKUS DALAM BAKSO MENGGUNAKAN PRIMER BERTARGET GEN CYTOCHROME C OXIDASE I - , R. ARINDRA HANURAGA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Security source of meat in the meatball should be maintained, because there still found many issues and cases of mixing meat sources in beef meatball with rat meat. This cases were against the law and also have the potential to transmit disease by rat vectors, such as plague and leptospirosis. Therefore, accurate detection needs to be done to respond to these problems. In this study, Real-Time PCR method was used and combined with High Resolution Melting Analysis (HRMA). A pair of primers was searched for amplifying the cytochrome c oxidase I (COI) gene sequences in mitochondrial DNA of a cow (Bos taurus) and rat (Rattus norvegicus). The sample consist of pure rat meat and beef, as well as models of rat and beef meatball mixtures with ratio of 0%, 5%, 10%, 15%, 25%, 50%, 75%, 100%. Sample preparation was done by extracting DNA from meat or meatballs, then tested its quality and quantity. The amplification of sequences was done with Real-Time PCR. The annealing temperature was optimized first, then followed by HRMA which observe the melt-specific peak (Tm) of its PCR products. The optimal annealing temperature was found 53,1oC. The melt-curve raw data were collected and then processed by HRMA to become normalized melt-curve, melt-peak, and melt-difference. The melt-curve showed the PCR product melting-regions of rat and cow around 81-82oC and 83-84,5oC. Melt-peak clarify the results by Tm 81,7oC and 83,6oC. The melt-difference curve of samples that compared to ratio 0% meatballs could saw the ratio of the meat mixture of rat meat in beef meatball samples.